Impact of 5G Technology in Efficent M-Edcation - Samanta, Pradip Kumar (International Journal of Computer Sciences and Engineering, 2025)
Today’s economy becomes more and more knowledge based, and education is a dynamic process of gaining and updating knowledge for individual to mass people throughout the globe. Education now a day’s required not only for the growing up and carrier oriented student but also for the qualified person who are in a very crucial position, for regular refreshing their present knowledge. To meet these requirements, the latest technology should be utilised for all round development of the present e- education system. So learning anytime anywhere, any one, and for anything, is required to be available through some mobile devices using efficient secured cloud computing integrated network. All these user requirements force to modify the present network architecture with the currently innovated 5G technology. In this paper we explore the mobile education scenario with 5G technology under design and implementation aspect.